Extrafiscalidade do IPVA como instrumento de proteção ambiental - Souza, Priscila Silva de (2012)
In recent years has increased markedly the number of vehicles circulating on the streets of cities across the country. These vehicles are responsible for emitting carbon dioxide into the atmosphere, what contributes to the increased pollution of the environment, which will affect long-term life of the community. Within this context, public health is threatened, since the pollution produced by discharges of cars brings respiratory diseases and destroys the ozone layer, causing prejudice also to the environment. The actions carried out by civil organizations in the fight against environmental pollution, cannot achieve together citizens the same results, if practiced by public authorities, by the limitation of its structure and scope. Thus, the figure of the State as promoter of environmental preservation in the use of his attributions, can avail themselves of the extrafiscalidade tribute to curb harmful conduct, committed by individuals. Thus, the tax levy on pre-existing legal solidarity becomes an important instrument to induce taxpayers to pay less tax, provided that they use for this, viable technologies to environmental health, reducing the emissions of pollutants from motor vehicles. In this sense, the Brazilian Government has sought to develop various programs, as it has already done so with the Proálcool, bio-fuel from sugar cane, with little environmental impact. To stimulate the purchase of vehicles moved to a bi-fuel, the State reduced the IPI tax rates at the time of purchase, making them more accessible to the consumer and thus reduced the emission of polluting agents. So, encourage the use of fuel with appropriate policies of low taxation should be the goal of the Brazilian Government, since it is the State's role to preserve the environment, together with the community, in accordance with art. 225 of CF/88. Soon, the system of taxation is no longer simply a mechanism for collection of financial resources to become an instrument of State action in the social field, enabling the legislator to discourage behaviors that may bring damage to society and the environment, and stimulate appropriate behaviors, bringing the citizen who fulfills its social role. Besides alcohol, science has discovered new clean sources of fuel, such as natural gas, electric power, hydrogen, among others, with reduced environmental impact. The aim of this study is to demonstrate how the State can, by making use of extrafiscalidade of tribute, promote the use of clean fuel sources by consumers/contributors through the gradation of aliquots of Property taxes for the less polluting modes; and yet, to the establishment of a differentiated policy for used vehicles, since these, notably, emit more toxic components in the atmosphere, due to its wear, always seeking the benefit of the collectivity.